KONSEP BID’AH MENURUT IMAM NAWAWI DAN SYEKH ABDUL AZIZ BIN BAZ - Mohamad Shafawi Bin Md Isa; Zaiyad Zaiyad (Universitas Islam Negeri Ar-Raniry, 2019)
The definition of bid'ah varies, causing conflict. The research question in this article is what is the meaning of sunnah and bid'ah according to Imam Nawawi and Syekh Abdul Aziz Bin Baz and what are the arguments used and the method of understanding them and the examples of bid'ah according to both. By using the library research method (library research) examines the data and written materials related to the theme of the problem being studied, using primary and secondary materials. The research found that, Imam Nawawi interpreted bid'ah as creating a practice that did not exist at the time of the Prophet, and he distributed bid'ah to two kinds, namely bid'ah ḥasanaḥ such as reading the talqin after burying a corpse and qabihaḥ such as raghaib prayer. Imam Nawawi concluded the hadith with hadith, which is a general hadith that is endorsed with a specific hadith, while Bin Baz defines bid'ah as any act of worship that is not practiced by the Prophet and there is no origin from the Qur'an, sunnah. and from the deeds of khulafa ar-Rashiddin, and he does not share bid'ah, all bid'ah is ḍhalalah, he also uses the term